Pengaruh Disiplin Kerja Dan Kepuasan Kerja Terhadap Produktivitas Karyawan Pt Aspirasi Hidup Indonesia Cabang Citra Raya: The Effect of Work Discipline and Job Satisfaction on Employee Productivity of PT Aspirasi Hidup Indonesia Citra Raya Branch - Aryo Widiyanto Roza; Herayati Herayati; Vicky Windasari (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze the influence of Work Discipline and Job Satisfaction on Employee Productivity (PT. Aspirasi Hidup Indonesia, Citra Raya Branch, Tangerang Regency). The number of samples in this study was 54 employees using saturated sampling. The researcher used a quantitative statistical research method and data processing was carried out using the IBM SPSS version 25 statistical application. The results of the study showed that Work Discipline partially had a significant and positive effect on Employee Productivity, with a t-count of 5,017> t-table 1.675 and a significance value of 0.00 <0.005. Partial Job Satisfaction also had a very significant and positive effect on Employee Productivity, with a t-count of 3,309 > t-table 1.675 and a significance value of 0.002 <0.005. Simultaneously, Work Discipline and Job Satisfaction have a significant influence on Employee Productivity, as evidenced by the results of Fcount 15,165 > Ftable 2.783 and a significant value of 0.000 <0.05. Based on the results of this study, it can be concluded that Work Discipline and Job Satisfaction are important factors that can significantly affect Employee Productivity at PT. Aspirasi Hidup Indonesia, Citra Raya Branch, Tangerang Regency.